2006
DOI: 10.1007/s10126-005-6185-8
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Class IIB Allele Polymorphism and Its Association with Resistance/Susceptibility to Vibrio anguillarum in Japanese Flounder (Paralichthys olivaceus)

Abstract: The full length of major histocompatibility complex (MHC) class IIB cDNA was cloned from a Chinese population of Paralichthys olivaceus by homology cloning and rapid amplification of cDNA ends-polymerase chain reaction (RACE-PCR). The MHC IIB genomic sequence is 1,864 bp long and consists of 34-bp 5'UTR, 741-bp open reading frame, 407-bp 3'UTR, 96-bp intron1, 392-bp intron2, 85-bp intron3, and 109-bp intron4. Phylogenetic analysis showed that the putative MHC class IIB amino acid of the Chinese P. olivaceus sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 52 publications
3
51
2
Order By: Relevance
“…For example, Palti et al [44] reported that MHCII alleles are significantly associated with anti-IHN in rainbow trout. Zhang et al [45] and Xu et al [46] successfully screened for anti-disease molecular markers by comparing the polymorphisms of Japanese flounder groups susceptible and resistant to Vibrio anguillarum.…”
Section: Qtl For Disease Resistancementioning
confidence: 99%
“…For example, Palti et al [44] reported that MHCII alleles are significantly associated with anti-IHN in rainbow trout. Zhang et al [45] and Xu et al [46] successfully screened for anti-disease molecular markers by comparing the polymorphisms of Japanese flounder groups susceptible and resistant to Vibrio anguillarum.…”
Section: Qtl For Disease Resistancementioning
confidence: 99%
“…Primers were designed from the sequence of a 3 0 -RACE-PCR product previously obtained by following the SMART-RACE protocol (Clontech, Saint-Germain-enLaye, F) using a conserved flatfish MHC class IIB forward primer (Zhang et al, 2006). This PCR product covered the region from the start of the exon 2 to the 3 0 -end of the transcript.…”
Section: Genotyping Of Mhc and Microbial Diversitymentioning
confidence: 99%
“…Inserts were amplified using M13 primers and sent out for sequencing (Microsynth, Balgen, CH). Sequences were aligned with Japanese Flounder sequences (Zhang et al, 2006) to identify putative exoneexon boundaries, which we then used to design internal exon 2 primers in conserved parts of the gene. PCR reactions contained 1 ml of undiluted DNA extract, 0.05 ml of Hot start taq (5 units ml…”
Section: Genotyping Of Mhc and Microbial Diversitymentioning
confidence: 99%
See 2 more Smart Citations